Manajemen Kurikulum Bidang Teaching and Learning (THUFULA, 2015)
This organizing the curriculum areas of teaching and learning studyapplies qualitative approach. The goal is to (1) describe the plan of curriculum planning in the field of teaching and learning, (2) describe the syllabus of curriculum in the field of teaching and learning, and (3) describe the lesson plans of curriculum in the field of teaching and learning at Islamic Studies State College of Kudus (STAIN Kudus).The results of this study are: (1) curriculum planning at STAIN Kudus approach is competence based, namely the approach to ensure subjects as teaching material oriented to the ability of learners / students, with three subjects of nuanced teaching and learning, namely Islamic Education System Planning, Learning Strategy of Islamic Education, Development of Islamic Education Evaluation System, (2) the syllabi of the three subjects allied the fields of teaching and learning but differed clearly from the aspect of its scope, however united integrative aspectsof the mastery of methods and leaning techniques, ( 3) the lesson plans of the three subjects clumped the field of teaching and learning are prepared with components subject code, types of subjects, programs of study, undergraduate scholarship, the weight of credit semester system, many meetings fourteen times, time according to the weight of the credit, the standard of competence , basic competencies,  indicators, subject matter, teaching methods, assessment systems, and learning resources.